2002
DOI: 10.1002/j.0022-0337.2002.66.3.tb03517.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Admission Criteria with Dental School Performance and Attrition

Abstract: This study was conducted to provide current information on the relationship between admission criteria and dental school performance, including the association of admission criteria and dental school outcomes such as remediation and attrition. Standard tests of bivariate association and multivariate regression models appropriate for continuous and discrete dependent variables were used to examine the relationship between multiple indicators of admission criteria and dental school performance for six recent cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
102
5
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 14 publications
15
102
5
3
Order By: Relevance
“…The results from the subsequent research investigating predictive validity of PAT, however, were not consistent. Although a few studies (e.g., Bellanti, Mayberry, & Tira, ; Gray & Deem, ) reported high correlation between PAT and preclinical grades in first‐year operative dentistry classes, a number of other studies found only weak to moderate correlations, suggesting that performance on PAT might not be a strong predictor of preclinical and clinical dental performance (Coy, McDougall, & Sneed, ; Curtis, Lind, Plesh, & Finzen, ; Hegarty, Keehner, Khooshabeh, & Montello, ; Oudshoorn, ; Ranney, Wilson, & Bennett, ; Sandow, Jones, Peek, Courts, & Watson, ). Moreover, Walcott, Knight, and Charlick () reported that PAT failed to significantly predict individual psychomotor performance on the first‐year operative dentistry exercises.…”
mentioning
confidence: 99%
“…The results from the subsequent research investigating predictive validity of PAT, however, were not consistent. Although a few studies (e.g., Bellanti, Mayberry, & Tira, ; Gray & Deem, ) reported high correlation between PAT and preclinical grades in first‐year operative dentistry classes, a number of other studies found only weak to moderate correlations, suggesting that performance on PAT might not be a strong predictor of preclinical and clinical dental performance (Coy, McDougall, & Sneed, ; Curtis, Lind, Plesh, & Finzen, ; Hegarty, Keehner, Khooshabeh, & Montello, ; Oudshoorn, ; Ranney, Wilson, & Bennett, ; Sandow, Jones, Peek, Courts, & Watson, ). Moreover, Walcott, Knight, and Charlick () reported that PAT failed to significantly predict individual psychomotor performance on the first‐year operative dentistry exercises.…”
mentioning
confidence: 99%
“…The computer skill GPA and high school score were the most consistent determinants of dental college overall AGPA, this is consistent with the findings of the previous studies. [3][4][5][6][7][8][9] The majority of students with high school scores greater than 90% did not encounter academic problems during their enrolment whereas about a quarter (23.2%) of students with a score in the range of 85-90% did encounter academic problems. However, 33.8% of students with a score less than 85% are warned students.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] Other studies have found a weak correlation and concluded that the interview score may be one factor among many that indicates the likelihood of success during the clinical years of dental school, or that the interview score may enable educators to better anticipate any academic problems that may arise as a student progresses through the curriculum. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] The marked differences that separate these studies may be readily attributed, however, to differences in the interviewing process as implemented by different schools. If dental schools are better able to identify students at risk, they may take active measures to prevent failure rather than rely on passive remedial measures after the fact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations